The formation of the low-sized high density plasma structures in the self-maintained plasma-beam discharge - Borisko, V.N.; Tseluyko, A.F.; Zinov’ev, D.V.; Lazurik, V.T.; Tarasov, I.K. (Вопросы атомной науки и техники, 2006)
The opportunity of use self-maintained plasma-beam discharge in an extended pulsing plasma diode of low pressure for making powerful sources of the soft X-rays is investigated. Conditions of formation of the self-maintained plasmabeam discharge are determined. The mode of making of dense high-temperature plasma on the basis of stannum ions in the discharge is shown. The stannum ions are used as a working element of a radiation sources at pulsing power of electron beam Ɋ~10…100 MW. Results of the examination on formation of the dense (np~1016 cm 3 ), small sizes (l<1 cm) plasma with the electron temperature Ɍe~100 eV in conditions of working material evaporation from the anode are given. The total contribution of energy to the discharge has made W < 20 J.